Anak dan Ruang Bermain: Telaah Terhadap Beberapa Penelitian Berbasis Affordances - Saragih, John Fredy Bobby (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Children’s response towards something is different from adults’. If an architect designs the foot of a monument with a beautiful arch, a child will respond it as a slide. When an architect designs a water pool as an aesthetic element of a monument area, a child will respond with a different return, which is a place to shower/swim and play, not for aesthetic. What is this phenomenon? And how can we understand this well? This story reassures us that between adults and children have different concepts of a building or space. With a descriptive approach to literature review, this article examines some affordance-based studies. From the few studies presented, it appears that affordances are not enough to understand why kids play on an informal play space. Semiotic approach can help to better understand why children play in informal spaces.